Alterations in the hypothalamic–pituitary–thyroid axis in animals submitted to early-life trauma - Machado, Tania Diniz; Dalle Molle, Roberta; Silveira, Patrícia Pelufo (Clinical and Biomedical Research, 2017)
Introduction: Changes in maternal care can affect offspring’s thyroid hormone T3 levels. Pups from highly caring mothers have higher levels of thyroid hormone T3. In humans, physical abuse in childhood is related to lower levels of T3 in adolescence. This study aimed at verifying if early-life trauma in rodents is correlated with T3 levels in adulthood. Methods: From the second day of life, litters of Wistar rats were subjected to reduced nesting material (Early–Life Stress-ELS) or standard care (Controls). In adult life, the animals were chronically exposed to standard diet or standard diet + palatable diet and plasma T3 levels were measured before and after the exposition to diet. Results: Thyroid hormone T3 levels in adult life correlated negatively with the licking and grooming (LG) scores in the ELS group. This correlation disappeared when the animals had the opportunity to choose between two diets chronically. Conclusion: The adverse environment affected maternal behavior and caused marks on the metabolism of the intervention group (T3), which were reverted by chronic palatable food consumption. Keywords: Trauma; T3; stress